Factors associated with cognitive flexibility in people with opioid-use disorder: a pilot study - Regier, Paul S.; Macedo de Arruda, Thais Costa; Sinko, Laura; Teitelman, Anne M.; Childress, Anna Rose (Frontiers in Psychiatry, 2024)
The ability to adapt to changing circumstances has strong survival value. Individuals with substance use disorders tend to get “stuck” over-responding to drug-reward signals and pursuing drugs despite negative consequences. A lack of flexibility may be tied to impairments in neurocognition, including learning, memory, and executive function. However, results are often mixed, potentially due to heterogeneity in factors such as mental health, personality traits, or prior adversity. This study aimed to identify which factors influence neurocognitive variations within the opioid use disorder (OUD) population. Based on prior literature, we hypothesized that individuals with OUD would show deficits (vs. controls) in one or more neurocognitive domains, and that these cognitive difficulties might be greater in individuals with other known contributors to impaired cognition. This pilot project included 32 individuals receiving medication for OUD and 15 non-substance using controls (NSC). Questionnaires assessed addiction and relapse risk factors, such as impulsiveness, social function, depressive symptoms, and childhood adversity. Neurocognitive performance was measured via the Penn Computerized Neurocognitive Battery (P-CNB), including tasks that probe attention, working memory, episodic memory, cognitive flexibility, and complex cognition, and was compared between the OUD and NSC groups. OUD participants (vs. NSCs) exhibited significantly lower performance on the conditional exclusion task (CET) (Accuracy: 1.11 vs. 2.38, p < 0.001) and the n-Back task (NBT) (F1 Scores: 83% vs. 95%, p < 0.001). Impulsiveness, social function, and depressive symptoms were highly inter-related; however, only higher impulsiveness (r = -.48, p = 0.006) and more social impairment (r = -.47, p = 0.007) significantly correlated with decreased CET (but not n-Back) performance. This pilot study suggests that working memory and cognitive flexibility are impaired in people with OUD and that impulsiveness and social function are key factors in cognitive flexibility impairments in people with OUD. These results may offer insights for larger-scale investigations and potential interventions to reduce relapse risk.